Pancreato-Hepatobiliary Malignancies: A Comprehensive Narrative Review of Epidemiology, Diagnosis, Multimodal Management, the Evolving Systemic Therapy Landscape, and Survival - Sophia Tsokkou; Menelaos Papakonstantinou; Paraskevi Chatzikomnitsa; Areti Danai Gkaitatzi; Evdokia Toutziari; Dimitrios Giakoustidis; Vasileios N. Papadopoulos; Alexandros Giakoustidis (Gastroenterology Insights, 2026)
Pancreato-hepatobiliary (HPB) malignancies—pancreatic ductal adenocarcinoma (PDAC), hepatocellular carcinoma (HCC), and the biliary tract cancers (BTC) comprising intrahepatic, perihilar and distal cholangiocarcinoma, gallbladder carcinoma, and ampullary adenocarcinoma—together constitute one of the heaviest and fastest-growing burdens in global oncology. Liver cancer is the third leading cause of cancer death worldwide, and pancreatic cancer, with a mortality-to-incidence ratio approaching unity, is projected to become the second leading cause of cancer death in high-income countries. This narrative review synthesises PubMed-indexed evidence across the full clinical arc of all three disease families, organised around epidemiology and risk; diagnosis, staging and biomarkers; surgical and multimodal management; and the rapidly evolving systemic therapy landscape, with survival and prognosis integrated throughout. Three cross-cutting narratives emerge. First, HPB cancers are united by late presentation, biological aggressiveness, and dependence on a background of organ dysfunction (cirrhosis in HCC, biliary obstruction in BTC and PDAC, and chronic pancreatitis as a major predisposing background in PDAC) that constrains therapy. Second, their trajectories are diverging: HCC has achieved the largest proportional survival gain of any solid tumour, driven by surveillance and immunotherapy in the subset of patients who reach specialist care; BTC has entered a nascent precision-oncology era in which FGFR2, IDH1, HER2, and BRAF alterations are druggable and immune-chemotherapy is first-line standard, although absolute survival gains remain modest and access to comprehensive molecular profiling is uneven; whereas PDAC has improved only incrementally, its immunosuppressive stroma and near-universal KRAS driver remaining formidable barriers. Third, molecular profiling, multidisciplinary care, and surgical centralisation are now non-negotiable structural determinants of outcome. We conclude that HPB oncology has entered a phase of real but unevenly distributed progress: long-term survival remains poor for most patients globally, and translating these advances into population-level gains will require earlier detection, broader access to molecular profiling and novel therapies, and biology-driven innovation.